Pedagogical mediation in virtual environments in the Costa Rican educational system - Calvo Barquero, Leslie Carolina (2021)
The framework of teaching practice is contextualized involved to understand the challenges in the field of learning and teaching processes during pandemic stages. A vision of teaching pedagogical mediation in times of pandemic in virtual environments is shown through the descriptive bibliographic review to follow the conception of pedagogical mediation in the 21st century and its implications in the face of technological challenges. The technological challenges around the World show to analyze the actions to keep on task the educational processes during COVID 19 and therefore in the face of a pandemic. This article wishes to substantiate the need to redesign pedagogical mediation processes with the application of strategies in virtual environments that allow the development of skills in students who participate in educational systems, particularly in the context of Costa Rican educational processes. The path developed by the Ministry of Public Education of Costa Rica promotes the skills and competence of the student, and therefore take into account their adaptation for the monitoring of digital tools in the application of pedagogical mediation in the contextualization of the curricular transformation that is being carried out in Costa Rica. The methodology of this article allows showing some authors' visions on mediation, virtual environments, and mediator teaching roles from a theoretical description. The proposal of the analyze of a mediator teacher in a virtual environment, given the educational response that has occurred in times of pandemic, can reflectively determine the pedagogical technological challenges that stimulate the change of educational paradigm.